Theoretical reduction of the incidence of colorectal cancer in Colombia from reduction in the population exposure to tobacco, alcohol, excess weight and sedentary lifestyle: a modelling study (2020)
Aims: To determine the potential impact fraction of alcohol and tobacco consumption, high body mass index and low physical activity on colorectal cancer burden in Colombia for the period 2016-2050. Methods: Based on age-specific and sex-specific data on colorectal cancer incidence, data from population-based surveys for the exposure data and population projections, the macrosimulation model Prevent V.3.01 was used to model expected colorectal cancer incidence for the period 2016-2050. Baseline models were those where exposure levels were not subject to change because of interventions. Two intervention scenarios were specified: one with elimination of exposure to the risk factor as of 2017 and a second one where over a 10-year period the current prevalence data gradually declined until they reach 90% of the 2016 levels. Results: Under the reference scenarios, a total number of 274 637 colorectal cancers would be expected to occur in the period 2016-2050. Under the scenario of 10% gradual decline in the prevalence of alcohol and tobacco consumption, physical inactivity and high body mass index, a total of 618, 488, 2954 and 2086 new cases, respectively, would be avoided. Under scenarios of elimination, these numbers of avoided cases would be 6908 (elimination alcohol), 6104 (elimination tobacco), 16 637 (optimizing physical inactivity) and 25 089 (all on ideal weight). Conclusions: In order to reduce the burden of colorectal cancer, it is important to take measures to halt the current trends of increasing sedentary behaviour and overweight in the Colombian population. Proportionally, alcohol and tobacco consumption are less important population risk factors for colorectal cancer.